2021
DOI: 10.3390/su132011535
|View full text |Cite
|
Sign up to set email alerts
|

Applying Spatial Analysis to Create Modern Rich Pictures for Grassland Health Analysis

Abstract: Grasslands are complex and heterogeneous ecosystems, and their health can be defined by the cumulative ability of their components to evolve, adapt, and maintain their integrity in the presence of stress/disturbance and provide ecosystem services. Herein, a design approach is used to generate alternative and multifunctional pastoral livestock production systems that enhance grassland health. As a way of understanding the complexity of grasslands and initiating the design process using systems thinking, rich pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…We used the Excel app from Microsoft 365 along with SAS JMP Pro 16.1.0 for graphing and statistical analysis. Because of the large spatial scales involved, analysis of extensive landscapes often relies on remote sensing and GIS [45][46][47]. Using 4-band imagery, plant health can be assessed using the Normalized Difference Vegetation Index (NDVI) [48].…”
Section: Analysis Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the Excel app from Microsoft 365 along with SAS JMP Pro 16.1.0 for graphing and statistical analysis. Because of the large spatial scales involved, analysis of extensive landscapes often relies on remote sensing and GIS [45][46][47]. Using 4-band imagery, plant health can be assessed using the Normalized Difference Vegetation Index (NDVI) [48].…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Because healthy vegetation with more chlorophyll reflects higher levels of light in the NIR and absorbs light in the red band, the NDVI distinguishes between areas of thick, healthy plant life vs. unhealthy and/or sparse plant life and has been used to both monitor plant health and drought conditions [49][50][51]. Researchers have shown that NDVI is directly related to the photosyn- Because of the large spatial scales involved, analysis of extensive landscapes often relies on remote sensing and GIS [45][46][47]. Using 4-band imagery, plant health can be assessed using the Normalized Difference Vegetation Index (NDVI) [48].…”
Section: Analysis Methodsmentioning
confidence: 99%
“…Another strategy is the use of Geographic Information Systems (GIS), a computational system that allows the analysis, creation, and management of spatial data. Geographic information systems are widely applied to Animal Science questions and can be used for land use/cover changes [ 223 ], land degradation [ 224 ] and grassland health assessment [ 4 , 8 ] by spatial analysis of multi-temporal data from a particular area. Geographic information systems generates a diverse range of information that can be integrated to produce useful outcomes that can contribute to the decision-making process [ 225 ] and allows the identification of suitable areas for specific purposes, such as adequate areas for specific plant species growth [ 226 ].…”
Section: Testable Design Process Hypothesismentioning
confidence: 99%
“…Ecosystem services are all the ecosystem functions and products that benefit and sustain human survival, life, and well-being, including the provision of food and water, pollination, regulation of climate, water and air, primary production and nutrient cycling, habitat for organisms, genetic resources, pharmaceuticals, and aesthetic/cultural values [ 5 , 6 , 7 ]. Therefore, grassland health can be defined as the ability of soils, microorganisms, flora, and fauna (including humans and grazing animals) present in the system to evolve, adapt and maintain their integrity in the presence of natural or human-caused stress/disturbance and provide essential components to sustain ecosystems [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation